Baculovirus coinfection strategy for improved galactosylation of recombinant glycoprotein produced by insect cell culture - Yap, Wei Ney; Abdul Rahman, Badarulhisam; Abdul Aziz, Azila (2005)
Baculovirus Expression Vector System (BEVS) is widely used for the production of recombinant glycoproteins, but it is not ideal for pharmaceutical glycoprotein production due to incomplete glycosylation. The factors that ensure successful glycosylation are the presence of sufficient amount of glycosyltransferases, sugar nucleotides as the substrate donor and the recombinant protein as the substrate acceptor. In this study, we analyze the galactosylation process by the introduction of - 1,4galactosyltransferase (-1,4GalT) as the glycosyltransferase of interest, and uridine-5’- diphosphogalactose (UDP-Gal) as the substrate donor. Recombinant human transferrin (rhTf) as a model protein was used as the substrate acceptor. Insect cell lines have been reported to produce a small amount of -1,4GalT and thus insufficient for effective galactosylation. In this study, we developed a method to produce galactosylated rhTf and optimized the expression of rhTf with better Nglycan quality. Recombinant -1,4GalT was introduced during protein expression by the coinfection of the BEVS with baculovirus carrying bovine -1,4GalT. To evaluate the extent of galactosylation by the coinfection strategy, a binding assay was established. In this binding assay, glycoprotein acceptor was absorbed onto ELISA plate surface. A lectin known as Ricinus communis agglutinin-I (RCA-I) labeled with peroxidase, was added and allowed to recognize Gal14GlcNAc group on the N-glycan of the glycoprotein, followed by appropriate color reaction measurements. Coexpression between rhTf and -1,4GalT did not show encouraging results due to the reduction of UDP-Gal upon baculovirus infection. This interesting finding suggested that the introduction of -1,4GalT alone was not sufficient for successful galactosylation. Alternatively, post harvest glycosylation method strategy seems to be a promising technique in the improvement of glycoprotein quality.